Podcast Komisi Pemilihan Umum Kabupaten Semarang sebagai Media Penyalur Informasi Kegiatan Pembentukan Penyelenggaraan Pemilu Badan Ad Hoc Tahun 2024 kepada Masyarakat - Geraldus Hugo Prasetyo; Khoirun Nisain Nafiah; Ninda Aulia Rahma; Ribka J.A. Warfandu; Putri Hergianasari; Maskup Asyadi (Universitas Kristen Satya Wacana Salatiga, 2022)
The General Election Commission is responsible for administering elections in Indonesia. This institution is assisted by an ad hoc committee to carry out the election process. But basically, this committee is not widely known by the public. This Institutional Practice Lecture Program is a community service project that uses podcast creation to increase student empathy and concern for the problems faced by the community and partner institutions. The podcast is made as a means of outreach to the public regarding the recruitment of Ad Hoc Committee and their tasks and then packaged in audio-visual to then be uploaded on the official digital platform of the General Election Commission of Semarang Regency. It is hoped that this Institutional Practice Lecture activity can contribute to the community and partner institutions in socializing the Recruitment of Ad Hoc Committee for the General Election Commission of Semarang Regency.